The Mediating Role of Project Citizenship Behavior in the Relationship Between Organizational Justice Dimensions and Project Success - Shafi, Muhammad Qaiser; Iqbal, Rimsha; Shahzad, Khurram; Unterhitzenberger, Christine (Project management journal, 2021)
The impact of behavioral aspects on project success remains an area that requires more attention. Drawing on the social exchange theory (SET), our study tested the mediating role of project citizenship behavior (PCB) in the relationships of all four organizational justice dimensions (i.e., procedural, distributive, informational, and interpersonal justice) with project success. A time-lagged survey of project team members (n = 233) was conducted and analyzed through structural equation modeling (SEM). The results indicate that all four organizational justice dimensions are positively associated with project success, whereas informational justice appears to be the most influential dimension, and that PCB mediates all of these relationships. Project managers/sponsors should enact organizational justice and enhance project citizenship to achieve project success.